The spatial dimension of risk : how geography shapes the emergence of riskscapes - Müller-Mahn, Hans-Detlef. (London ; New York : Routledge/Earthscan, 2013)
"Through its exploration of the spatial dimensions of risk, this book offers a brand new approach to theorizing risk, and significant improvements in how to manage, tolerate and take risks. A broad range of risks are examined, including natural hazards, climate change, political violence, and state failure"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Human geography; Spatial behavior; Risk -- Sociological aspects; Risk perception; Risk management; Electronic books